2018
DOI: 10.1016/j.ddtec.2018.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Log P as a tool in intramolecular hydrogen bond considerations

Abstract: Intramolecular hydrogen bonding (IMHB) considerations are gaining relevance in drug discovery and a molecular descriptor which can predict very early the capacity of a compound to form IMHB is needed to speed up the optimization process of drug candidates. Although log P is largely used for optimization purposes, in this paper we firstly use the Block Relevance (BR) analysis to theoretically show how log P is not a convenient choice to assess IMHB properties of candidates. Then we discuss the limits of log P a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 21 publications
0
25
0
Order By: Relevance
“…Previously we reported am etric called lipophilic permeability efficiency (LPE), which quantifies the efficiencyw ith which ac ompound achieves passive membrane permeability at agiven ALogP-defined lipophilicity. [15] LPE is derived from the difference between the experimental hydrocarbon-water partition coefficient, LogD(dd/w), which reflects amolecules net hydrogen bond acidity in its membrane-associated conformation, [16] and ALogP,w hich reflects ac ompoundsm inimum lipophilic character in the aqueous environment. [15] LPE, defined specifically by the equation LPE = logD(dd/ w)À1.06AlogP + 5.47, represents as caffoldsi ntrinsic membrane permeability by normalizing its membrane partitioning against its bulk lipophilicity.…”
Section: Resultsmentioning
confidence: 99%
“…Previously we reported am etric called lipophilic permeability efficiency (LPE), which quantifies the efficiencyw ith which ac ompound achieves passive membrane permeability at agiven ALogP-defined lipophilicity. [15] LPE is derived from the difference between the experimental hydrocarbon-water partition coefficient, LogD(dd/w), which reflects amolecules net hydrogen bond acidity in its membrane-associated conformation, [16] and ALogP,w hich reflects ac ompoundsm inimum lipophilic character in the aqueous environment. [15] LPE, defined specifically by the equation LPE = logD(dd/ w)À1.06AlogP + 5.47, represents as caffoldsi ntrinsic membrane permeability by normalizing its membrane partitioning against its bulk lipophilicity.…”
Section: Resultsmentioning
confidence: 99%
“…4). In a previous study it was shown that nelfinavir has a larger propensity to form IMHBs than indinavir [30] and thus it was expected that Δlog P oct-tol , EPSA and log K w IAM of nelfinavir are smaller than the correspondent values determined for indinavir. This was verified for Δlog P oct-tol and log K w IAM but not for EPSA, which fails in ranking the polarity of the two protease inhibitors; probably because of the high and different number of HBA groups present in the structures.…”
Section: Br Analysis and Polarity Descriptorsmentioning
confidence: 87%
“…Using the molecular modeling and the application of the different theoretical methods we can calculate some properties: ξHOMO, ξLUMO, (Santos et al, 2019) the Dipole Moment (Lindic et al, 2019), Log (P) (Caron et al, 2018), the solubility... of three bioactive molecules.…”
Section: Methods and Computational Detailsmentioning
confidence: 99%